2021
DOI: 10.1108/itse-10-2020-0218
|View full text |Cite
|
Sign up to set email alerts
|

Are Japanese university students ready for remote language learning?

Abstract: Purpose The purpose of this study is to assess Japanese university students’ readiness for taking e-learning language courses. The focus is placed on students’ self-analysis of their abilities to use their smart devices for remote language learning activities. Design/methodology/approach Japanese university students’ readiness for the shift towards remote learning has been measured by a self-reported online survey. The question items are based on three categories of Gay’s e-readiness models (2018). The surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…As we can see from the results of Table 2, especially the financial readiness, which only scores 3.12 (not ready, needs some work). This finding corresponds with [3,14,18], which mentioned that many students had access to smartphones yet could not afford the cost of internet connectivity. When asked about their favourite learning apps, the percentages for Google Classroom and WhatsApp were almost similar (48% and 47%).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…As we can see from the results of Table 2, especially the financial readiness, which only scores 3.12 (not ready, needs some work). This finding corresponds with [3,14,18], which mentioned that many students had access to smartphones yet could not afford the cost of internet connectivity. When asked about their favourite learning apps, the percentages for Google Classroom and WhatsApp were almost similar (48% and 47%).…”
Section: Discussionsupporting
confidence: 76%
“…Researchers have begun to explore the implementation of e-learning as an alternate approach [9,14]. E-learning uses digital technology to create educational resources for teaching and learning, instruct learners, and govern courses to obtain a high percentage of student academic achievement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Learning Japanese through the internet can improve learning effectiveness, while also reducing learning time and economic costs. The learning difficulty in the online environment is relatively high, thus requiring more self-directed learning and self-restraint abilities [19]. At the same time, increasing interaction and communication in the online environment can enhance students' deep understanding of Japanese language knowledge.…”
Section: Collaborative Learning Strategiesmentioning
confidence: 99%
“…98% Finland university students owned mobile phones and as well discover that mobile learning has taken a greater step in the digital revolution. Also, Hirata (2021) revealed that the majority of university students on campus in Japan carry mobile phones, and contemporary students tend to be checking their emails and entering information into their mobile phones. Mobile learning has a lot of benefits and the technology has a greater place for teaching in the nearest future.…”
Section: Introductionmentioning
confidence: 99%